P468 The association of symptoms with viable vaginal or rectal Chlamydia trachomatis load: multicenter cohort study (FemCure). (14th July 2019) - Janssen, Kevin; Wolffs, Petra; Hoebe, Christian; Heijman, Titia; Götz, Hannelore; Vries, Henry De; Bruisten, Sylvia; Dukers-Muijrers, Nicole
Abstract : Background: Symptoms have been associated with Chlamydia trachomatis (CT) infections in culture-based studies, in contrast to studies based on nucleic acid amplification tests (NAAT). This may be because NAAT also detect non-viable bacteria. As culturing techniques are insensitive, we developed a sensitive polymerase chain reaction (V-PCR) technique to measure the viable bacterial load. We here assess the association between symptoms and viable load in 524 women with vaginal or rectal CT. Methods: Prior to treatment at three STI clinics, we included NAAT-CT-positive adult women (n=411 vaginal and rectal CT; n=88 only vaginal CT; n=25 only rectal CT), who were negative for HIV, syphilis and Neisseria gonorrhoeae (Netherlands, 2016–2017; FemCure). We assessed the viable rectal and vaginal load (log10 CT/ml) using V-PCR. We present the mean viable load (range 0 [non-viable] to 6.5) and tested associations with vaginal symptoms (coital lower abdominal pain, coital blood loss, intermenstrual bleeding, altered discharge, painful or frequent micturition) and rectal symptoms (discharge, pain, blood loss), using multivariable regression techniques adjusting for age and educational level. Results: Of 499 vaginal CT NAAT-positive women, mean viable load was 3.5 log10 CT/ml (SD: 1.6). Vaginal symptoms were reported by 50.3% (n=251) of women; women reporting any vaginal symptoms had higher vaginal viable load (mean 3.6 log10 CT/ml) than women without symptoms (mean 3.3 log10 CT/ml) (B=0.35, p=0.012) (mainly due to 'altered discharge'). Of 436 rectal CT NAAT-positive women mean viable load was 2.2 log10 CT/ml (SD: 2.0); rectal symptoms were reported by 4.8% (n=21) and not associated with rectal viable load. Conclusion: In an outpatient clinical setting, women diagnosed with vaginal CT have a higher viable load when they have symptoms. Yet, the difference is quite small (0.3 log10 CT/ml) and is therefore unlikely to have a major impact on clinical patient management in women. Disclosure: No significant relationships.